Are temporary oil supply shocks real? - Johan Brannlund; Geoffrey Dunbar; Reinhard Ellwanger (Bank of Canada, 2022)
Hurricanes disrupt oil production in the Gulf of Mexico because producers shut in oil platforms to safeguard lives and prevent damage. We examine the effects of these temporary oil supply shocks on real economic activity in the United States. We find no evidence that temporary oil supply shocks affect state-level employment or indirectly affect industrial production in sectors not immediately related to oil production. We find that the temporary oil supply shocks have local, temporary price effects-mainly on gasoline prices-and that broader consumer price index inflation is also temporarily affected. In addition, we find no effect on imports, exports, exchange rates or the import price of oil. Our results suggest that oil reserves held by US refineries are largely sufficient to absorb any temporary disruptions to production.
Keywords: E31; E32; Q31; Q41; Q43; 330; Business fluctuations and cycles; Inflation and prices